1989
DOI: 10.1111/j.1438-8677.1989.tb00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Content of Algae under Stress*

Abstract: The distribution of the phytohormone, abscisic acid (ABA), within the phylum ofPhycophyta was investigated by an enzyme-linked immunoassay (ELISA). Of 64 algal species tested (originating from 9 divisions, 20 classes and 36 orders, including procaryotes) all species contained ABA, whereas no ABA could be detected in the bacteria Escherichia coli, Rhodospirilhm rubrum, and Halobacterium halobium. It is concluded that ABA is universally distributed within the algal kingdom and is not restricted to cormophytes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 41 publications
4
62
0
Order By: Relevance
“…The ABA content ranged from c. 50-2000 pmol g −" d. wt for hydrated thalli, corresponding to an ABA content in the range of c. 20-700 pmol g −" f. wt. This is about an order of magnitude higher than the ABA content of nonstressed algal cells (3-34 pmol g −" f. wt weight ; Hirsch, Hartung & Gimmler, 1989). Conversely, some fungi have substantially higher ABA contents (up to 7800 pmol g −" d. wt ; Kettner & Do$ rffling, 1987 ; Crocoll, Kettner & Do$ rffling, 1991).…”
Section: mentioning
confidence: 92%
See 2 more Smart Citations
“…The ABA content ranged from c. 50-2000 pmol g −" d. wt for hydrated thalli, corresponding to an ABA content in the range of c. 20-700 pmol g −" f. wt. This is about an order of magnitude higher than the ABA content of nonstressed algal cells (3-34 pmol g −" f. wt weight ; Hirsch, Hartung & Gimmler, 1989). Conversely, some fungi have substantially higher ABA contents (up to 7800 pmol g −" d. wt ; Kettner & Do$ rffling, 1987 ; Crocoll, Kettner & Do$ rffling, 1991).…”
Section: mentioning
confidence: 92%
“…But only c. 5 % of the total intracellular label was found in ABA metabolites and a relatively high percentage of labelled products was released into the medium (Hirsch et al, 1989). Also, cyanobacteria might release high amounts of ABA into the surrounding medium.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…GC-MS studies have shown the presence of ABA in several algal species, such as Dunaliella parva, Chlamydomonas reinhardtii, Ulva lactuca, Draparnaldia mutabilis and Chara foetida (Bradley, 1991). Furthermore, tests of 64 algal species revealed an accumulation of ABA under adverse environmental conditions (Hirsch et al, 1989). Similar effects are seen in bacteria (Cohen et al, 2008) and higher plants; ABA accumulates in the tissues of plants grown under water-, osmotic-or salt-stress conditions, and can act as an important stress-alleviating factor (Creelman & Zeevaart, 1985;LaRosa et al, 1985;Stewart et al, 1986;Bensen et al, 1988;Zeevaart & Creelman, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…in o CM in o reported to be present in various cyanobacteria (Hirsch et al, 1989). Measurement of the ABA levels in Anabaena 7120 revealed very low levels of ABA that did not exceed 0.2 /*M and did not change with increasing Sue (data not shown).…”
mentioning
confidence: 79%